Cervical balloon combined with oxytocin improves clinical efficacy and safety for induction of labor with scarred uterus - Dongmei Ji; Juhua Ding; Xiaoqiong Li; Gang Li; Dong Yin (IMR Press, 2022)
Background: To evaluate cervical balloon combined with oxytocin improves clinical efficacy and safety for induction of labor with scarred uterus. Methods: The clinical data of pregnant women undergoing vaginal trial delivery after cesarean section in Huai'an Maternal and Child Health Hospital, from January 2020 to January 2021 were retrospectively analyzed. Among them, 80 pregnant women with scarred uterus who were induced by cervical balloon combined with oxytocin were considered as CBO group. 80 pregnant women with natural delivery scar uterus were considered as control, who were matched to CBO group for age, gestational age, and pre-pregnancy BMI. In CBO group, Bishop score before and after induction of labor was compared. Between the CBO and control groups, mode of delivery and duration of labor were analyzed, and maternal and infant outcomes were compared. Results: The overall effective rate of cervical maturation after labor induction was 88.8%, and the proportion of vaginal delivery in the CBO group were significantly higher than that in the control group. Besides, the induced labor time, first stage of labor time and the total stage of labor time in the CBO group were significantly shorter than those in the control group. There was no significant difference in maternal and infant outcomes between the two groups. Conclusion: Cervical balloon combined with oxytocin could significantly improve the clinical effect of parturients with scar uterine without increasing maternal and infant complications, which is a safe and effective strategy that can be applied in clinical practice.